Bio-inspired multiple-stimuli responsive porous materials with switchable flexibility and programmable shape morphing capability. (May 2020) - Sun, Yan; Kim, Min-Kyeom; Wang, Mei; Yu, Jianmin; Hong, Sung Yong; Nam, Jae-Do; Ci, Lijie; Suhr, Jonghwan
Abstract: Inspired by desert resurrection plant, Rose of Jericho, this study developed a new porous material with programmable multiple-stimuli responsive features. The first one is reversible shape-memory transformation of experiencing extremely large deformations upon dehydration and rehydration; superior to the plant, the aerogels display controllable responsiveness based on moisture amount with fast actuation. The second one is switchable flexibility depending on the polarity of exposed fluids; these aerogels are reversibly compressible with outstanding flexibility in polar solvents but sustain incompressibility with high stiffness in nonpolar solvents. The third one is programmable shape morphing capability driven by imbibition of liquid droplet; mimicking the movement of the plant but in different mechanisms, the aerogels can evolve into programmed V-shape or U-shape by simply controlling the liquid imbibition location. These multiple-stimuli responsive features arise from the unique ensemble of the porous morphology, and the interactions between solvent molecules and the chemical structures of the porous material engineered by two-step crosslinking mechanism. It can be foreseen that the synergistic effect of the intriguing features could allow for the applications of the aerogels as smart sensors/actuators, soft robotics, and biomedical devices, all of which typically require smart adaptability to external stimuli and/or extreme environments. Graphical abstract: Image 1